Pest categorisation of Citrus tristeza virus (non‐European isolates). (31st October 2017) - ,; Jeger, Michael; Bragard, Claude; Caffier, David; Dehnen‐Schmutz, Katharina; Gilioli, Gianni; Gregoire, Jean‐Claude; Jaques Miret, Josep Anton; MacLeod, Alan; Navajas Navarro, Maria; Niere, Björn; Parnell, Stephen; et al.
Abstract: The Panel on Plant Health performed a pest categorisation of non‐European isolates of Citrus tristeza virus (CTV) for the EU territory. CTV is a well characterised virus for which efficient detection assays are available. It is transmitted by vegetative multiplication of infected hosts and by aphid vectors. The most efficient one, Toxoptera citricida, has limited EU presence but another one, Aphis gossypii, is broadly distributed. CTV is reported from a range of countries outside the EU and EU isolates are present in seven of the eight citrus‐growing member states. Non‐EU isolates are not known to occur in the EU and therefore do not meet one of the criteria for being a Union regulated non‐quarantine pest. The natural host range of CTV is restricted to Citrus, Fortunella and Poncirus species. CTV non‐EU isolates are listed in Annex IIAI of Directive 2000/29/EC and the main pathway for entry, plants for planting, is closed by the existing legislation. CTV isolates may therefore only enter through minor alternative pathways. They have the potential to subsequently spread through plants for planting and through the action of aphid vectors. CTV non‐EU isolates are able to cause severe symptoms on a range of citrus crops that EU isolates do not induce. Overall, non‐EU CTV isolates meet all the criteria evaluated by EFSA to qualify as Union quarantine pests. The main knowledge gaps and uncertainties concern (1) the status of Rutaceae species other than Citrus, Fortunella and Poncirus as natural hosts for CTV; (2) the potential undetected presence of non‐EU CTV isolates in the EU and in particular the prevalence and biological properties of CTV isolates that may be present in ornamental citrus; and (3) the inability of EU CTV isolates apparently related to non‐European stem pitting (SP) isolates to cause SP in sweet orange.